2003
DOI: 10.1007/s00701-002-1030-6
|View full text |Cite
|
Sign up to set email alerts
|

Debulking or biopsy of malignant glioma in elderly people – a randomised study

Abstract: Longer survival time is achieved after open craniotomy and resection of tumour. However, overall benefit of open surgery to patient seems to be modest, while time of deterioration did not differ between two treatment groups. Our results support previous studies on the benefit of radiotherapy in the treatment of malignant glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
192
1
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(212 citation statements)
references
References 10 publications
10
192
1
9
Order By: Relevance
“…The results indicated the survival benefit of resection (5.7 months) versus biopsy (2.8 months). Although, the study was unblinded and without adjuvant chemotherapy 11 . Chaichana et al compared 133 and 72 consecutive patients aged 65 years and older who underwent surgery and needle biopsy for intracranial primary (de novo) GBM and were retrospectively reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated the survival benefit of resection (5.7 months) versus biopsy (2.8 months). Although, the study was unblinded and without adjuvant chemotherapy 11 . Chaichana et al compared 133 and 72 consecutive patients aged 65 years and older who underwent surgery and needle biopsy for intracranial primary (de novo) GBM and were retrospectively reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Not only OS but also time of deterioration and quality of life are important outcome measures if we discuss fatal disease. Vuorinen et al suggested that there was 2.8 times higher risk for deterioration after biopsy than after craniotomy and resection 11 . Pereira et al used AC and somato-sensory evoked potentials (SSEPs).…”
Section: Discussionmentioning
confidence: 99%
“…A recent small randomized trial included 23 patients aged greater than 65 years with malignant glioma assigned to only biopsy or resection with radiation therapy. 43) The median survival time was significantly longer in patients who underwent resection (5.6 months) than in those who underwent biopsy (2.8 months). In general, surgical treatment for elderly patients carries the risk of high mortality and morbidity.…”
Section: Discussionmentioning
confidence: 92%
“…However, little evidence for these therapies is available as most studies investigated only small or retrospective patient cohorts [18][19][20][21][22][23][24][25]. Furthermore, availability of stereotactic radiotherapy or radiosurgery and financial resources of health care systems account for significant differences in use between countries and even national regions.…”
Section: Introductionmentioning
confidence: 99%